Nucleoside Inhibitors of Zika Virus - Eyer, Luděk; Nencka, Radim; Huvarová, Ivana; Palus, Martin; Joao Alves, Maria; Gould, Ernest A; De Clercq, Erik; Růžek, Daniel (The Journal of infectious diseases, 2016)
There is growing evidence that Zika virus (ZIKV) can cause devastating infant brain defects and other neurological disorders in humans. However, no specific antiviral therapy is available at present. We tested a series of 2'-C- or 2'-O-methyl-substituted nucleosides, 2'-C-fluoro-2'-C-methyl-substituted nucleosides, 3'-O-methyl-substituted nucleosides, 3'-deoxynucleosides, derivatives with 4'-C-azido substitution, heterobase-modified nucleosides, and neplanocins for their ability to inhibit ZIKV replication in cell culture. Antiviral activity was identified when 2'-C-methylated nucleosides were tested, suggesting that these compounds might represent promising lead candidates for further development of specific antivirals against ZIKV.
Keywords: therapy; flavivirus; Cercopithecus aethiops; replikace viru; Nucleosides; nucleoside analogue; antivirové látky; nukleosidy; Microbial Sensitivity Tests; Zika virus; Chlorocebus aethiops; Animals; Antiviral Agents; Virus Replication; zvířata; mikrobiální testy citlivosti; Vero Cells; antiviral; virus zika; Vero buňky; Zika Virus